2017
DOI: 10.1007/s10072-017-2987-5
|View full text |Cite
|
Sign up to set email alerts
|

Sildenafil-related cerebral venous sinus thrombosis and papilledema: a case report of a rare entity

Abstract: We present a rare case of cerebral venous sinus thrombosis associated with long-term and high-dose use of sildenafil. A 29-year-old man was referred to our neuroophthalmology clinic for bilateral visual deterioration and severe headache. He had stage 2 papilledema and other clinical and neurological examinations were normal. He had used the drug for nearly 2 years, two to three times a day. All laboratory parameters including blood count cell, coagulation panels, and genetic tests including methylene-tetrahydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…In parallel with the biochemical marker results, histological anomalies were observed in the testes of the SIL-treated rats. Our results are consistent with many studies that have reported a number of deleterious effects on testicular histology associated with high-dose and/or long-term administration of SIL [ 35 , 57 60 ]. Similarly, deleterious histopathological changes of SIL in testis have been demonstrated, including disruption of the epithelial lining of the seminiferous tubules, destruction of the testis, impaired spermatogenesis, and the presence of inflammatory cells [ 61 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In parallel with the biochemical marker results, histological anomalies were observed in the testes of the SIL-treated rats. Our results are consistent with many studies that have reported a number of deleterious effects on testicular histology associated with high-dose and/or long-term administration of SIL [ 35 , 57 60 ]. Similarly, deleterious histopathological changes of SIL in testis have been demonstrated, including disruption of the epithelial lining of the seminiferous tubules, destruction of the testis, impaired spermatogenesis, and the presence of inflammatory cells [ 61 ].…”
Section: Discussionsupporting
confidence: 93%
“…Numerous studies have shown that the recreational abuses for a long time of these medications have led to several negative effects on different organs including liver, kidney, cardiac, stomach, pituitary gland and testes [ 34 – 37 ]. A rare case of cerebral venous sinus thrombosis (CVST) associated with long-term and high-dose SILwas reported [ 35 ]. Central retinal artery occlusion associated with SIL overdose has recently been reported [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, sildenafil has been reported to have various adverse effects, including venous thrombosis. Table 1 shows previous reports on the association between venous thrombosis and oral sildenafil [ 5 , 8 , 9 ]. According to previous reports, the mechanisms of vascular thrombosis may be due to vascular stasis and/or platelet aggregation resulting from long-term sildenafil use.…”
Section: Discussionmentioning
confidence: 99%
“…CVT is three times more frequent in women than in men and several risk factors for CVT have been identified: some are general risk factors for venous thromboembolism (VTE) such as hereditary thrombophilia, use of oral contraceptives, cancer, pregnancy and puerperium, and others are specific risk factors to CVT, such as head injury, dural arteriovenous fistula, head and neck infections, spontaneous intracranial hypotension and dehydration 1 4–7. Very well-established pharmacological risk factors for CVT are oral contraception and hormone replacement therapy4 8; conversely CVT has sporadically been reported as adverse drug reaction (ADR) with other drugs such as anabolic androgenic steroids, corticosteroids, erythropoietin, sildenafil, l-asparaginase and dexamethasone among others 9–15. Within illicit drugs, CVT has been reported to be related to cocaine use 16…”
Section: Introductionmentioning
confidence: 99%